Awareness of Dyscalculia Among Educators and Stakeholders in Malaysia - Sai hoe fu (SEA-CECCEP, 2024)
Despite the growing recognition of dyscalculia as a significant learning difficulty, awareness among educators remains a concern. This study delves into the awareness of dyscalculia among educators in Malaysia, aiming to shed light on its prevalence and implications for students' learning outcomes. Employing a survey methodology, data were collected from 153 educators and stakeholders across various fields. Descriptive statistics were utilized to analyze the data. The findings reveal that as of 2023, a staggering 47.1% of respondents in Malaysia still lack awareness of dyscalculia. This highlights a crucial gap in understanding within the educational community, potentially hindering support for students with dyscalculia. These results underscore the urgent need for targeted interventions to enhance dyscalculia awareness among educators. Addressing this gap could lead to improved identification and support for students with dyscalculia, ultimately enhancing educational equity and outcomes. This study underscores the importance of incorporating dyscalculia awareness into educational policy and practice to ensure inclusive and effective learning environments for all students.